The Effect of Quantitative Easing on Inflation in Korea - Min-Ho Nam (East Asian Economic Review (EAER), 2018)
This paper evaluates the whole impact of quantitative easing on inflation in Korea implemented by the central banks in four major advanced economies, the U.S., Euro Area, U.K. and Japan. According to the analysis employing a VAR-X model with the security holdings of those central banks an exogenous variable, quantitative easing is estimated to exert downward pressures on inflation in Korea. Considering the impulse responses of Korean macroeconomic variables to a quantitative easing shock, the spillover effect is transmitted through exchange rate channel while trade channel turns out to be ineffective. In an additional analysis assessing the impact of each quantitative easing program of the central banks, only those of the Fed and European Central Bank are estimated to be significant. The empirical results prove to be robust even if using long-term interest rates as an alternative indicator of quantitative easing.
Keywords: E31; E58; F42; 330; Quantitative Easing; Security Holdings; Spillover Effects; Exchange Rate and Trade Channel; Inflation in Korea; VAR-X